Design and evaluation of a mobile phone-based health intervention for patients with hypertensive condition. (October 2016) - Sun, Na; Rau, Pei-Luen Patrick; Li, Yunqiu; Owen, Tom; Thimbleby, Harold
Abstract: The objective of this study is to design and evaluate a mobile phone-based intervention which helps users to identify factors that lead to abnormal blood pressure and to motivate them to adopt a healthier lifestyle. An exploratory longitudinal study was conducted to discover the changes of patients' self-management behaviors and their attitude toward the application during the intervention. 20 Chinese patients with hypertensive or pre-hypertensive condition were invited to use the application for 6 weeks, and semi-structured interviews with each participant were carried out every two weeks. The results indicated that participants' attitude toward the application improved a lot during the study. Participants' attitude toward self-reflection and perceived control over that behavior stayed unchanged in the first two weeks of intervention and then increased significantly in the following two weeks. Similar change was found in participants' attitude and perceived behavior control in maintaining a healthy lifestyle. The interview data revealed that the mobile self-reflective intervention motivated Chinese patients to abandon inappropriate beliefs and to modify their health beliefs by the knowledge gained from their own experience. Highlights: A mobile health intervention was designed to motivate self-reflective behavior. Users' attitude toward self-reflective behavior was improved significantly. Users perceived more control over daily behaviors by the end of the intervention. Users modified health beliefs based on their own experience after the intervention.